Atrial reverse remodeling: Restitution of early tachycardia-induced alterations of atrial ion currents after termination of rapid atrial pacing in rabbits - Laszlo, Roman; Konior, Agnes; Bentz, Kerstin; Eick, Christian; Schreiner, Birgit; Schreieck, Juergen; Bosch, Ralph F. (Research in veterinary science, 2013)
Studies report on the reversal of electrophysiological parameters altered by atrial tachycardia after cessation of the latter. However, there is no data concerning reversal of tachycardia-induced alterations of ion currents. Reverse remodeling of atrial ion currents (ICa,L, Ito, Isus) was studied in our rabbit model of tachycardia-induced electrical remodeling. Three groups each with four animals were built. Rapid atrial pacing (600/min) for 5days was applied in all groups. Thereafter, different time intervals (5, 10, 20days) were awaited before the patch clamp experiments. Similar to Ito remodeling in our model, within 20days after cessation of atrial tachycardia, time course of Ito reverse remodeling was also U-shaped. In contrast, there was no significant recovery of ICa,L which was initially reduced by rapid atrial pacing. Relevance of a missing recovery of ICa,L is likely as this current is closely linked with intracellular calcium handling.